Postabortion contraceptive use among women in Nepal: results from a longitudinal cohort study - Sunita Karki; Mahesh C. Puri; Anupama Ale Magar; Diana Greene Foster; Sarah Raifman; Dev Maharjan; Nadia Diamond-Smith (Reproductive Health)
Abstract Introduction Although the Government of Nepal has developed strategies to integrate contraceptive services with abortion care to better meet the contraceptive needs of women, data indicate that significant gaps in services remain. This paper assessed post-abortion contraceptive use, trends over 36 -months, and factors influencing usage. Methods Data from this paper came from an ongoing cohort study of 1831 women who sought an abortion from one of the sampled 22 government-approved health facilities across Nepal. Women were interviewed eight times over 36 months between April 2019 to Dec 2023. Bivariate and multivariate analysis were used to analyze the data. Results Results show that after abortion, 59% of women used modern contraception, with injection being the most prevalent method, followed by condoms, pills, implants, and IUD. The hazard model showed that discontinuation of modern contraception was significantly higher among women desiring additional children (aHR 0.62) and lower among literate (aHR − 0.15) and those with existing children (aHR − 0.30). Women’s age, ethnicity, cohabitation with husband, household’s income and autonomy were not associated with continuation. Conclusion After having an abortion, we found that just slightly more than half of women used modern methods of contraception; this percentage did not increase significantly over the course of three years.